2015
DOI: 10.1590/0004-282x20150081
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality of ischemic stroke subtypes in Joinville, Brazil: a population-based study

Abstract: Previous population-based studies reported the incidence and mortality of ischemic stroke (IS) subtypes in different settings, most of them on the White population from high-income countries 1,2,3,4,5,6,7,8 . In Latin America, there is only one study, which was conducted in a Spanish and Mestizo population in Iquique, Chile 9. As far as we know, no previous study has reported IS subtypes rates among predominantly White people from Latin America.The crude annual incidence rate of IS in Brazil range from 62 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
4
9
0
2
Order By: Relevance
“…The frequency of young adults observed in this study, whose age group included individuals aged between 18 to 50 years is close to those found in other Brazilian studies, ranging from 16 to 41% 6,11,18 . In studies conducted in developed countries, who consider the young adult population between 18 and 45 years old 4,19,20 the incidence ranges from 5 to 10%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The frequency of young adults observed in this study, whose age group included individuals aged between 18 to 50 years is close to those found in other Brazilian studies, ranging from 16 to 41% 6,11,18 . In studies conducted in developed countries, who consider the young adult population between 18 and 45 years old 4,19,20 the incidence ranges from 5 to 10%.…”
Section: Discussionsupporting
confidence: 90%
“…In this study the majority of patients at the time of admission showed a moderate stroke severity according to the NIHSS, which is in consonance with Rena et al 9 2014, a study conducted on a stroke unit in Italy, which evaluated 150 patients young adults. When compared the types of stroke, the greater frequency of ischemic stroke in this study corroborates to what has been described in the literature 3,4,18,19,22 , in particular, the proportion of patients diagnosed with hemorrhagic stroke were mostly of hypertensive etiology, reasoning with the findings of previous studies 3,4 . There was a statistically significant difference when comparing female and male with hypertensive etiology of hemorrhagic stroke: the most hypertensive were men, presenting higher frequency of hemorrhagic stroke.…”
supporting
confidence: 92%
“…Stroke is the third main cause of death worldwide and one of the main causes of permanent disability among adults in developed countries [ 1 , 2 , 3 ]. In Brazil, the incidence of ischemic stroke varies from 105 to 137/100,000 inhabitants, and patients with stroke exhibit high prevalence rates of ischemic heart disease, hypertension, and diabetes mellitus [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A tomografia computadorizada (TC) é uma ferramenta utilizada para melhor definição diagnóstica na doença cerebrovascular; entretanto não está disponível no Hospital Regional de Coari, enquanto fica disponível 24 horas por dia em todos hospitais regionais de Joinville/SC, por exemplo. 20,21 Apesar da escala NIHSS não ser recomendada para pacientes crônicos, 22 alguns estudos a utilizaram e revelaram um comportamento semelhante da pontuação entre regiões. Estudos em Natal/RN observaram uma média de 5 pontos, 23,24 enquanto um estudo em Campinas/SP observou uma média de pontos de 1,61 em pacientes com AVC crônico.…”
Section: Resultsunclassified